Acute hemodynamic impact of atrioventricular delay and left ventricular pacing vector programming in MultiPoint Pacing. Issue 5 (11th April 2022) - Hua, Wei; Cai, Lin; Su, Yangang; Xu, Wei; Shen, Farong; Wang, Jingfeng; Gu, Min; Badie, Nima; Jiang, Chunlan; Zhang, Shu
Abstract: Background: The benefits of cardiac resynchronization therapy (CRT) in heart failure patients have been shown to depend on device programming, particularly atrioventricular delay (AVD) and left ventricular (LV) pacing site selection. This study compared the hemodynamic AVD optimization for commonly used biventricular (BiV) and MultiPoint Pacing(MPP, Abbott) LV vector selection strategies. Methods: After de novo CRT‐D (Abbott Quadra Assura MP) and quadripolar LV lead (Abbott Quartet) implant, acute LV pressure was measured across a range of AVDs (60–225 ms) in four pacing modes: BiV with most proximal cathode, BiV with most distal cathode, MPP using two cathodes with earliest and latest right ventricle (RV)–LV activation times, and MPP using two cathodes with maximal anatomical separation. Hemodynamic improvement was evaluated by changes in maximum LV pressure first‐derivative versus RV pacing (Δ dP / dt ). Results: Twenty patients (64 years old, 68% male) completed the acute pacing protocol at six centers in China. Hemodynamic improvement versus RV pacing for BiV (proximal), BiV (Distal), MPP (electrical), and MPP (anatomical) was 22.1% ± 13.6%, 23.7% ± 13.4%, 24.5% ± 13.4%, and 25.1% ± 13.9%, respectively. The best MPP setting was marginally superior to the best BiV across all patients (25.8% ± 13.4% vs. 24.5% ± 13.1%, p = .040) and in the majority of patients (75.0% vs. 25.0%, p = .004). AVD programmed as little as 20 ms from optimum significantly reduced the Δ dP / dt benefit for all modes. Conclusions: The maximal hemodynamic improvement across AV delays in this population was greater with MPP than BiV. Furthermore, patient‐specific AVD programming was critical in achieving the full hemodynamic response for all BiV and MPP modes.